2020
DOI: 10.1155/2020/2156762
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Systemic Lupus Erythematosus with Cirrhosis

Abstract: Aim. Cirrhosis is rare in systemic lupus erythematosus (SLE) patients with a poor prognosis. This study is aimed at retrospectively analyzing our single-center experience to explore the characteristics of cirrhosis in SLE patients. Methods. SLE patients with cirrhosis from 2012 to 2019 were enrolled. SLE diagnosis was rigorously confirmed by a medical record review according to the revised 1997 American College of Rheumatology classification criteria for SLE. The diagnosis of liver cirrhosis was based on a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 19 publications
1
9
2
Order By: Relevance
“…The AST to ALT ratio is frequently calculated for predicting fibrosis stage or clinical outcomes in chronic hepatitis [29,30]. It was reported that globulin is positively associate with mortality in patients with cirrhosis [31]. Serum gamma-globulin ≥18 g/L is a significant predictor of disease progression, tumor development and death for cirrhotic patients [32].…”
Section: Discussionmentioning
confidence: 99%
“…The AST to ALT ratio is frequently calculated for predicting fibrosis stage or clinical outcomes in chronic hepatitis [29,30]. It was reported that globulin is positively associate with mortality in patients with cirrhosis [31]. Serum gamma-globulin ≥18 g/L is a significant predictor of disease progression, tumor development and death for cirrhotic patients [32].…”
Section: Discussionmentioning
confidence: 99%
“…other liver diseases, such as fat infiltration and overlapping autoimmune liver disease, virus infection, and alcoholism [6][7][8][9][10][11]. End-stage liver disease complicated with portal hypertension, cirrhosis, and hepatic encephalopathy is a rare complication of SLE unless there are nonalcoholic fatty liver disease (NAFLD), viral hepatitis, or autoimmune hepatitis (AIH) that existed simultaneously [3,6].…”
Section: Introductionmentioning
confidence: 99%
“…other liver diseases, such as fat infiltration and overlapping autoimmune liver disease, virus infection, and alcoholism [6][7][8][9][10][11]. End-stage liver disease complicated with portal hypertension, cirrhosis, and hepatic encephalopathy is a rare complication of SLE unless there are nonalcoholic fatty liver disease (NAFLD), viral hepatitis, or autoimmune hepatitis (AIH) that existed simultaneously [3,6]. It has been revealed that a few patients with end-stage liver disease, accompanied with portal hypertension and cirrhosis, did not die of liver failure, while the main cause of death was infection or cancer [4].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic liver disease can also have overlapping features of systemic lupus erythematosus (SLE), such as arthralgia, cytopenia, and coagulation abnormalities, when seen with positive serologies and low complements, and can be confused for active SLE. Hypocomplementemia can be seen due to the low production of complement proteins [3]. Systemic lupus erythematosus (SLE) is an autoimmune disorder that can affect multiple organ systems including the kidneys, lungs, joints, bone marrow, and skin.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic liver disease can also have overlapping features of systemic lupus erythematosus (SLE), such as arthralgia, cytopenia, and coagulation abnormalities, when seen with positive serologies and low complements, and can be confused for active SLE. Hypocomplementemia can be seen due to the low production of complement proteins [ 3 ].…”
Section: Introductionmentioning
confidence: 99%